Dalit leadership in panchayats - Narender Kumar (Jaipur, 2006)
This study is based on the field survey carried out in four states of India on the emerging Dalit leadership in panchayats after the 73rd Constitution Amendment Act. It concentrates on some of the issues like: What have been experiences so far of Dalit leaders in panchayats? How do they perceive their newfound role? What are enabling and inhibiting factors? What changes these affirmative actions have brought out at ground levels? What needs to be done to make Dalit leadership more effective so that it brings out positive changes in quality of life of its people? Though, situations in different states vary but still there are certain common factors. While education, experience, family, community, economic independence and personal initiatives have been found to be enabling factors for the effectiveness of Dalit leadership, caste practices is the most important inhibiting factor in all the states. But, like many other studies, this study has also recognized the potential of Dalit leadership in panchayats. These local leaders have capacities to bring those irreversible positive changes in our social system, which could not be achieved by democratically elected state and union governments.
Keywords: Dalit-India